Livestock supply to an imperial sacrificial site of the early Chinese empires evidenced by strontium isotope ratios - Tang, Zihua; Wang, Xueye; Xiao, Jun; Chen, Xianglong; Hu, Songmei; Yang, Miaomiao; Tian, Yaqi; Yuan, Jing (Frontiers in Earth Science, 2022)
A newly excavated ritual site, Xuechi, exposed abundant sacrificial livestock, allowing to understand the supplies and managements of livestock during the early Chinese Qin-Han Empires. Here we reported animal enamel 87Sr/86Sr values from the Xuechi site that are obviously higher than those of local snails and surface water, as well as calcites of the Chinese Loess Plateau (CLP) where the site was located, strongly suggesting that these sacrificial animals were not raised in the vicinity of the site. The regional bioavailable 87Sr/86Sr isoscape further indicates that some livestock were probably derived more than one hundred kilometers away, suggesting a complex social network for recruiting and managing the sacrificial activities. In the context of other Neolithic-Bronze Age records on the CLP, an increasing trend in variation of faunal 87Sr/86Sr values shows a robust correlation to Chinese states' trajectory, in concordance with the territorial expansion model for state formation.